High-efficiency 2.45 and 5.8 GHz dual-band rectifier design with modulated input signals and a wide input power range - Sara El Mattar; Abdennaceur Baghdad (Institute of Advanced Engineering and Science, 2023)
This paper presents a new rectifier design for radio frequency (RF) energy harvesting by adopting a particular circuit topology to achieve two objectives at the same time. First, work with modulated input signal sources instead of only continuous waveform (CW) signals. Second, operate with a wide input power range using the Wilkinson power divider (WPD) and two different rectifier diodes (HSMS2852 and SMS7630) instead of using active components. According to the comparison with dual-band rectifiers presented in the literature, the designed rectifier is a high-efficiency rectifier for wide RF power input ranges. A peak of 67.041% and 49.089% was reached for 2.45 and 5.8 GHz, respectively, for CW as the input signal. An efficiency of 72.325% and 45.935% is obtained with a 16 QAM modulated input signal for the operating frequencies, respectively, 69.979% and 54.579% for 8PSK. The results obtained demonstrate that energy recovery systems can use modulated signals. Therefore, the use of a modulated signal over a CW signal may have additional benefits.